Are exercise programs relevant in psychiatric wards? - I. Valada; I. Caldas; S. Vieira; I. Pereira (European Psychiatry, 2022)
Introduction About 3% of the general population suffers from Severe Mental Illness (SMI), including schizophrenia spectrum, bipolar and major depressive disorders. In this group, the rates of cardiovascular disease, diabetes mellitus and metabolic syndrome are approximately twice as high as the general population and the life expectancy is 13-30 years inferior compared to age and sex matched controls, greatly due to medical comorbidities. Low levels of physical activity (PA) and low fitness are likely to play a role.